A dynamical model for the calcineurin‐NFATc signaling pathway and muscle fiber shifting. Issue 1 (25th January 2021) - Villota-Narvaez, Yesid; Ramírez-Martínez, Angélica; Garzón-Alvarado, Diego; Röhrle, Oliver
Abstract: Training exercise produces skeletal muscle adaptation: at the organ scale, as anatomical changes; and at the myofiber scale, as mitochondrial and protein type content. The protein content of a myofiber is controlled by the calcineurin‐NFATc signaling pathway: exercise triggers the pathway, and its final product is the translocation of dephosphorylated NFATc to the nucleus. Once in the nucleus, NFATc controls the state of the gene program to encode the slow or the fast fiber type characteristics. In the long term, the adaptation of the fiber type characteristics produces a shift in muscle fiber type: an increase in the number of myofibers of the fast type (which means that myofibers of the slow type shift to fast type) is related to force production; and an increase in the number of myofibers of the slow type (myofibers of the fast type shift to slow type) is related to fatigue resistance. These macroscopic features, i.e. force production and fatigue resistance, are the main target of most training protocols; however, little attention is focused on the limitations imposed by the fiber distribution of muscles at the organ scale. Based on the calcineurin‐NFATc signaling pathway, we represented an exercise stimulus by a cytosolic calcium signal, and simulated the dynamics of NFATc in the nucleus. In this contribution, we present a dynamical model for the calcineurin‐NFATc signaling pathway to describe the time course of dephosphorilated NFATc in the nucleus. We used an experimental report of a continuous stimulation pattern for calibration, and an experimental report of a pulsed stimulation pattern for comparison; we obtained a good agreement between the simulations and the experimental measurements.